The Effect of Combined Use of Platelet-Rich Plasma and Adipose-Derived Stem Cells on Fat Graft Survival. Issue 5 (May 2015) - Seyhan, Nevra; Alhan, Dogan; Ural, Ali Ugur; Gunal, Armagan; Avunduk, Mustafa Cihad; Savaci, Nedim
Abstract : Background: Free fat grafts have an unpredictable survival rate that limits their successful use. To increase the viability of fat grafts, it is important to minimize the reabsorption rate. Objective: Our aim was to investigate whether the combined use of platelet-rich plasma (PRP) and adipose derived stem cells (ADSCs) would contribute an improvement in lower resorption rates of fat grafts. Methods: Inbred Fischer 344 rats were randomized into 4 groups (n = 10). Fat grafts were mixed with Dulbecco modified Eagle medium in group A, with PRP in group B, with ADSC in group C, and with PRP + ADSC in group D and were injected to the scalp. In vitro growth factor (vascular endothelial growth factor, transforming growth factor-β, and fibroblast growth factor) levels were compared using enzyme-linked immunoassay method. After 12 weeks weight, volume and histology of the transplants were evaluated. Results: The mean weight and volume of the fat grafts were highest in group D. Histopathological investigations revealed that the number of viable adipocytes and blood vessels were highest in group D. The level of growth factors was significantly higher in stem cell plus PRP group. Conclusion: Adipose-derived stem cells combined with PRP can enhance the survival of transplanted fat tissue.